Growth of PbS nanopyramidal particulate films for potential applications in quantum-dot photovoltaics and nanoantennas - Hawaldar, Ranjit R.; Mulik, Uttam P.; Patil, K.; Pasricha, R.; Sathaye, S.; Lewis, A.; Amalnerkar, Dinesh P. (Materials Research Bulletin, 2005)
We report a simple interfacial process called the liquid-liquid interface reaction technique (LLIRT) that leads to the formation of nanosized PbS particulate films with hitherto unreported pyramidal morphology. The resultant PbS films were characterized by transmission electron microscopy (TEM) with selected area electron diffraction (SAED), X-ray diffractometery (XRD), atomic force microscopy (AFM), near field scanning optical microscopy (NSOM) and UV-vis spectroscopy. The pyramidal morphology is speculated to originate from the preferred orientation of the 2 2 0 plane of cubic PbS. Our nanopyramidal PbS particulate films display remarkably sharp excitonic peak centered around 656 nm that accounts for a band gap of 1.8 eV suggesting, in turn, their potential application in QD photovoltaics. Interestingly, the feasibility of such nanopyramids to potentially act as nanoantennas (as revealed by the NSOM) is also suggested. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Atomic force microscopy; Chemical synthesis; Electron microscopy; Nanostructures; Optical properties

Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

Nanocrystalline Mn-Zn-ferrite by novel oxalato-hydrazinated complex method - Kanade, K. G.; Amalnerkar, Dinesh P.; Potdar, H. S.; Kale, B. B. (Materials Chemistry and Physics, 2009)
We report here for the first time the synthesis of technologically important ferrite, using a metal oxalato-hydrazinate (MOH) complex method. The MOH complex of iron-manganese-zinc was synthesized at room temperature using the precursors, ferrous ammonium sulphate, manganese acetate and zinc acetate. Thermo-gravimetric studies of MOH intermediate showed complete phase formation of MnZnFe(2)O(4) at 280 degrees C. XRD data showed the formation of single phase cubic spinel MnZnFe(2)O(4). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) demonstrate the spherical shape particle morphology. TEM images indicated the particle size of ferrite powder in the range of 20-36 nm. Magnetization of synthesized nano-sized Mn(0.69)Zn(.0.19)Fe(2.12)O(4) was observed coercive force (H(c)) at 127.82 Oe with a saturation magnetization (M(s)), 34.5 emu g(-1) using vibrating sample magnetometer (VSM) at room temperature. Mossbauer study of nano-sized ferrite powder showed super-paramagnteic behavior. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic materials; Mn-Zn-ferrite; Nanostructures; Optical properties